Triage of Acute Ischemic Stroke in Confirmed COVID-19: Large Vessel Occlusion Associated With Coronavirus Infection - Moshayedi, Pouria; Ryan, Timothy E.; Mejia, Lucido Luciano Ponce; Nour, May; Liebeskind, David S. (Frontiers in Neurology, 2020)
Outbreak of COVID-19 has posed a significant challenge to the global healthcare. Acute stroke care requires rapid bedside attendance, imaging and intervention. However for acute stroke patients who have diagnosis of, or under investigation for, COVID-19 the concern for nosocomial transmission moderates operational procedures for acute stroke care. Here we present our experience with an in-hospital stroke code called on a COVID-19 positive patient with left middle cerebral artery syndrome and our challenges for a timely exam and imaging, and decision to intervene. Outlook of involvement with the COVID-19 pandemic necessitates development of protocols to sustain timely and effective acute stroke care while mitigating healthcare-associated transmission.